Marketing, psychological and social factors influencing blood donation: A case of South African Millennials - Dabula, Nandi (My University, 2020)
The disparity between blood supply and demand is a grave concern for the healthcare sector globally, including South Africa. According to the South African National Blood Services for example, less than 1% of South Africans are regular blood donors; yet an estimated eight out of ten people will need blood during their lives. These facts draw attention to the exigent need for incessant recruitment of new blood donors and the retention of existing blood donors to meet the demand for blood in South Africa. A good source of donors can be the millennials, who are large in size and can easily influence and mobilise their peers through their high social media presence and engagements. The factors that would however influence millennials’ blood donation attitudes and intention is yet to be studied. Studies have assessed blood donation awareness, attitudes and motivations. While these psychological factors provide some explanation of blood donation, there is limited knowledge on the driving roles of social media marketing and social factors. Also limited are insights into the behavioural outcomes of attitudes toward blood donation, especially among a large, but fickle consumer segment like the millennials. This study therefore had three main objectives: 1) to examine the impact of social media marketing in terms of communications posted on its various platforms on awareness, perceptions, motivations, peers, family, attitudes and behavioural intention to donate blood, 2) to assess the extent to which some psychological and social factors impact on millennials’ attitude towards blood donation. 3) to examine the extent to which the attitude influences millennials’ behavioural intention to donate blood. To achieve these objectives, a conceptual model was developed guided by the social cognitive theory which posits that learning occurs in a social environment with some mutual interactions, the Health Belief Model suggesting psychological drivers of health-related behaviour and the Theory of Planned Behaviour suggesting the relationship between attitude and behavioural intention. The testing of the conceptual model with fifteen proposed hypotheses required quantitative methods. Data was collected from 650 respondents with self-administered questionnaires from the University of the Witwatersrand, Gauteng Province in South Africa. For the empirical testing of the hypothesised relationships in the model, a structural equation modelling was applied, utilising the AMOS 23 software. The study results revealed that out of the fifteen hypotheses tested, fourteen were supported. Specifically, social media marketing was found to have a positive effect on both psychological factors (i.e. awareness and motivation),social factors (i.e. peer and family groups) and on attitudes and behavioural intention. Out of the three psychological factors that were examined, motivation and awareness and not perception positively and significant influenced attitudes. Attitudes positively influenced blood donation intention. The research contribution is twofold. Firstly, and theoretically, by examining the impact of social media marketing, psychological and social factors on blood donation attitude and behavioural intention, this study contributes to contextual knowledge of social marketing as well as social media marketing literature. For example, it revealed that even for a health and life-saving product like blood, social media marketing can aid social marketers’ efforts to build attitudes and propensity to act. Secondly, by revealing that social media marketing does create blood donation awareness and motivations among millennials and affect their peers and family, social marketers can use these findings to intensify the dissemination of blood donation information in all social media sites. These sites could include Twitter, YouTube, Facebook and even Instagram. These study findings also provide valuable insights to blood banks, social marketers, NPO’s, marketers, academics and policy makers particularly from a perspective of understanding Millennials and their attitudes towards prosocial behaviour such as blood donation. With the attitude positively impacting on behavioural intention as found in this study, these stakeholders should find ways to incentivise this large market segment of millennials to convert their intention into actual behaviour.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) (Marketing) for the Department of Marketing, School of Economic and Business Sciences, Faculty of Commerce, Law and Management, University of the Witwatersrand
Keywords: Blood--Transfusion; Blood donors--South Africa; Blood banks|zSouth Africa--Planning.